Submission to Vera Commission - Anne Owers (Washington University Journal of Law & Policy, 2006)
This Essay describes the function and methodology of the Inspectorate of Prisons in England and Wales, and the importance of its role in the independent scrutiny of conditions and treatment in prisons and other places of detention.
Keywords: Prison accountability; Executive oversight; Detention; Prison administration; United Kingdom